Gemeinschaft and Gesellschaft: The Geopolitics of Academic Plagiarism - Bennett, Karen (2012)
This chapter uses Tönnies’ notions of Gemeinschaft and Gesellschaft to examine the issue of plagiarism from a culturalist perspective. According to this, plagiarism is understood not as a universal or unequivocal evil, but as one component of a particular ethical system that took hold within a specific historical and social context, roughly contemporary with the European Enlightenment. Today, that ethical framework is so deeply entrenched in the power structures of the modern world that its values go largely unquestioned in countries at the centre of the world economic system. However, as we move away from the centre towards the periphery, we find that those values become weaker, and may enter into conflict with another moral code, which is usually more traditional in nature, though no less coherent. Indeed, in some parts of the world, it is those traditional values that actually hold sway in local universities, raising serious problems for academic mobility and the internationalization of knowledge. The very concept of plagiarism is also full of inherent contradictions, caused, at least in part, by historical tensions generated by the passage from one kind of society to the other. Vestiges of the Gemeinschaft continue to penetrate all aspects of modern university culture, ranging from teaching practices (the persistence of imitatio in academic writing courses) and hierarchical relations (the power balance inherent in the tutor/student dynamic) to the very philosophy of knowledge underlying modern science (where the rhetorical implications of the citation procedure sit uncomfortably alongside a metadiscourse of transcendental truth). Hence, this chapter argues that, in a context of increased globalization, there is a need for a deeper understanding of the various dynamics at work in this complex concept.